Pemanfaatan Vlog Sebagai Komunikasi Interpersonal (Studi Deskriptif Kualitatif Album Ke-7 Endank Soekamti â€œSoekamti Dayâ€) - Giantika, Gan Gan (Jurnal Komunikasi, 2018)
Increased Internet usage makes artists use the internet as a media campaign and maintain its existence in the community, the medium that is in great demand by famous people is a vlog on youtube , many artists use this media as a promotional tool and the artist's daily information to fulfill information for his fans. One of them who use is indie band Endank Soekamti. The band's group utilized vlogs as a means of promoting their new album. The purpose of this research is to know the process of utilization of vlog as interpersonal communication medium in 7 Kean Soekamti's "Soekamti Day" Promotion. The type of research used in this study is to use the type of research descriptive qualitative study, by trying to interpret data research describes in detail a message or a particular text. The results of research on the use of vlog as a medium of interpersonal communication in promoting the new album Endank Soekamti is a positive statement, feelings of responsibility, presence, feedback, spontaneous reaction, feelings of free opinion, attention, honesty of openness in the process of interpersonal communication on this album. So that the audience can like and give a response seen many who see the vlog and provide comments as one form of responseloves the latest album from Endank Soekamti, it's also because the daily life is very simple, relaxed and free impressed, it shows that the band is very open in building communication in vlog.Â Keywords: Communication Interpersonal, Vlog, Content Analysis.